PEMBERDAYAAN MUTU PENDIDIKAN MELALUI BIMBINGAN BELAJAR UNTUK MENINGKATKAN LITERASI DAN NUMERASI DI DESA KLURAHAN - Sya'idun; Muhammad Ulil Abror; Mohamad Azhar Annawa UBM; Yahya Raihan; Doni Assibli Mahmud; Wahyu Dimas Saputra; Naufal Diama Putra; Sri Wulandari; Rohmatul Fauziah; Dinatus Zahro; Kholi Sotus Sariroh; Alvina Tri Nur Cahyanti; Nera Ayu Jayanti (Abdimas IAI Ngawi, 2025)
The literacy and numeracy skills of elementary school children in Klurahan Village are still relatively low, due to low motivation to learn, lack of variety in teaching methods, and limited involvement of parents and supporting facilities. To address these issues, students from the Ngawi Islamic Institute conducted a tutoring program through a Community Empowerment Practicum (PPM) in July 2025. This study employed a descriptive qualitative approach with 30 students from grades I–VI at Klurahan Elementary School and Nurul Islam Klurahan Islamic School as subjects, who participated in 13 sessions. The program was implemented through the stages of problem identification, planning, implementation, and evaluation, using a contextual, participatory, and enjoyable learning approach. The results showed an improvement in students' basic skills in reading, writing, and arithmetic, as well as a higher enthusiasm for learning. The results indicated an improvement in children's basic skills in reading, writing, and arithmetic, as well as the development of a learning spirit. The evaluation also noted positive changes in learning habits, although these were not yet uniform. Challenges faced include irregular attendance and limited parental involvement. This program makes a tangible contribution to improving the quality of basic education in rural areas and is relevant for sustainable development through cross-sectoral collaboration. Keywords: tutoring, literacy, numeracy, basic education, community empowerment   Abstrak: Kemampuan literasi dan numerasi anak sekolah dasar di Desa Klurahan masih tergolong rendah, disebabkan oleh rendahnya motivasi belajar, metode pembelajaran yang kurang variatif, serta terbatasnya peran orang tua dan sarana pendukung. Untuk menjawab permasalahan tersebut, mahasiswa Institut Agama Islam Ngawi melaksanakan program bimbingan belajar melalui kegiatan Praktikum Pemberdayaan Masyarakat (PPM) pada Juli 2025. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan subjek 30 anak kelas I–VI yang berasal dari SDN Klurahan dan MI Nurul Islam Klurahan, yang mengikuti 13 kali pertemuan. Program dilaksanakan melalui tahapan identifikasi masalah, perencanaan, pelaksanaan, dan evaluasi, dengan pendekatan pembelajaran kontekstual, partisipatif, dan menyenangkan. Hasilnya menunjukkan peningkatan kemampuan dasar siswa dalam membaca, menulis, dan berhitung, serta munculnya semangat belajar yang lebih tinggi. Hasilnya menunjukkan adanya peningkatan kemampuan dasar anak dalam membaca, menulis, dan berhitung, serta tumbuhnya semangat belajar. Evaluasi juga mencatat perubahan positif dalam kebiasaan belajar meskipun belum merata. Tantangan yang dihadapi meliputi ketidakteraturan kehadiran dan minimnya keterlibatan orang tua. Program ini memberikan kontribusi nyata terhadap peningkatan mutu pembelajaran dasar di wilayah pedesaan dan relevan untuk dikembangkan secara berkelanjutan melalui kolaborasi lintas sektor. Kata Kunci: bimbingan belajar, literasi, numerasi, pendidikan dasar, pemberdayaan masyarakat